Nested Halbach Arrays of Rectangular, Cylindrical, and Polygonal Magnets Optimize the Field-Free Line in Magnetic Particle Imaging - Ergor, Melike; Olamat, Ali; Dogan, Nurcan; Bingolbali, Ayhan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
Magnetic particle imaging (MPI) provides three-dimensional decoding of magnetic materials. In MPI, the field-free line (FFL) selection field method offers a spatial encoding across a line, which reduces acquisition time, improves sensitivity, and increases the signal-to-noise ratio. Permanent magnets of Halbach layout are interesting for the use in MPI owing to their advantages, such as an alternative way for the generation of a magnetic field and reducing power consumption. Therefore, an ideal Halbach magnet was iterated using identical bar magnets that were positioned and oriented based on the analytical formulations in the literature. In this letter, we suggest multishapes (rectangular, polygonal, and cylindrical) as one-layer, two-layer, and three-layer nested models of Halbach arrays that generate FFL at different gradients. The stability and gradient of the MPI system have been improved by using multiple-layer Halbach arrays with FFL-based design. Analytical and simulation results were compatible with each other for all designs. Here, we show that the gradient has been improved 30% by using polygonal magnet shapes; particularly, the octagon shape provided an acceptable result among the other polygonal shapes. For the three-layer configuration, a 95% homogeny gradient field was achieved in 50 mm stability.
Keywords: Hard magnetic materials; magnetic particle imaging; field-free line; Halbach magnets; gradient field; DESIGN; NMR; Engineering; Physics